Michael Servetus’s Britain: Anatomy of a Renaissance Geographer’s Writing - Hughes, Peter (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
Michael Servetus was a theologian, physician, astrologer, and editor. In the latter capacity he edited two editions of Ptolemy’s Geographia, to which he added some apparatus and several articles that described European countries and peoples. Following in the footsteps of medieval and Renaissance geographical writers before him, Servetus did his research less by travelling and more by reading. His “original” pieces, like the works of the authors upon whom he drew, were thus a patchwork of quotations and borrowings from earlier books. This article examines both what Servetus said about Great Britain, a place he never visited, and the nature and quality of the information that he, his predecessors, and his followers provided for their readers. Such an examination helps us understand the way a learned polymath such as Servetus worked in composing his heretical critique of the Trinity and in gaining the insights that led him to make the first European description of the circulation of blood through the lungs.